ANALISIS PENGARUH ATRIBUT PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KAMERA DIGITAL CANON (STUDI KASUS KOMUNITAS FOTOGRAFI MUSI DI PALEMBANG) - M SYAFRAN RINALDIE; ISLAHUDDIN DAUD; AHMAD WIDAD (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2013)
The study objective was to determine the influence of product attributesand brand image of the Canon digital camera purchase decision, either partially or simultaneouslyThe method used in this research is as much as 77 census respondents. Analytical techniques used in this research is the analysis of qualitative and quantitative analysis.The results showed that the variable product attributes are most influentialon purchase decisions is variable product features. Product quality, product design and brand image does not significantly influence the purchase decision. Therefore, companies should be more active to maintain and create new innovations for its products.Keywords: product attributes, brand image, purchase decision